Web‐based GIS for live GV of land generation through utilitarian association rule mining and multiple regression analysis for Chennai district. (25th January 2019) - Srinivasan, K.; Murugasan, R.
Summary: In this paper, the Guideline Value (GV) of land is automatically generated via a utilitarian model, which consists of a multilevel regression predictor and an association rule. The utilitarian model generates GV for the Chennai area land in Tamil Nadu, India. In the existing system, the land GV is fixed based on the market price. The GV is revised according to market analysis, every 2 years, and creates an anomaly in price, causing loss to the government of Tamil Nadu. In the utilitarian GV pricing model, with the survey number or the street name entered in the website, the GV generates automatically. The automatic generation of the GV in the website is based on the real‐time calculation of the distance between the spatial and environmental parameters and the type of land use collected through a geographical information system. From the result, the utilitarian model provides 85% accuracy in the automated GV generation of land. The accuracy is evaluated through the Buyer Acceptance Testing (BAT) for the present and utilitarian guideline value.